Digestive comorbidity in patients with rheumatic diseases: Not only NSAID-induced gastropathy - A. E. Karateev; N. V. Gontarenko; A. V. Tsurgan (Научно-практическая ревматология, 2016)
Digestive comorbidity is a serious problem that significantly aggravates the course of rheumatic diseases. Diseases of the gastrointestinal tract (GIT), liver, and pancreatobiliary system may present a threat to life and substantially worsen its quality. The incidence of many digestive diseases, such as gastric ulcer (including its complicated forms), cholelithiasis, and acute pancreatitis, in patients with rheumatic diseases (at least in those with rheumatoid arthritis) is considerably higher than in the population. The presence of this comorbidity poses substantial challenges during active anti-rheumatic therapy. Rheumatologists are very familiar with issues in the prevention of GIT complications due to the use of nonsteroidal anti-inflammatory drugs. However, new time presents new challenges. The widespread use of immunosuppressive agents and biologic agents requires careful monitoring of complications associated with liver and bowel diseases. This review considers a relationship of rheumatic diseases and anti-rheumatic therapy to comorbidities, such as cholelithiasis, acute pancreatitis, viral hepatitis B and C, and intestinal diverticula.